Pengaruh Celebrity Endorser, Harga Produk, dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Pada Produk Minuman Sprite - Salsabila Alfi Ayu Shahara; Nur Hidayati; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the influence of celebrity endorsers, product prices, and electronic word of mouth on purchasing decisions on sprite beverage products. The research used is a quantitative method. The population in this study were students of the Faculty of Economics and Business, Islamic University of Malang, class of 2019. Meanwhile, the sample used in this study was purposive sampling using the slovin formula, so there were 90 samples. The data used is primary data by using a questionnaire. The recording evaluation approach used is instrument test: validity and reliability test, normality test, conventional assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, speculation test: simultaneous test, partial test and willingness coefficient.From the results of the research partially obtained results that celebrity endorser has no effect on purchasing decisions, product prices have no effect on purchasing decisions, and electronic word of mouth has a significant effect on purchasing decisions. While simultaneously celebrity endorser, product price, and electronic word of mouth have a significant effect on purchasing decisions. Keywords : Celebrity Endorser, Product Price, Electronic Word of Mouth, Purchase Decision